Development of mandatory & voluntary instruments of sustainability reporting (SR) according to carrots & sticks 2006 - 2016 - Ririn Breliastiti (STIE Perbanas Surabaya, 2020)
Sustainability Reporting (SR) has become the main report of the world’s leading companies. In 2005, it was found that more than 250 top companies listed on the Fortune 500 had prepared SR separately from the Annual Report in which the number in each country varies. In the developed countries, awareness to compile and issue SR is supported by government regulations so that SR becomes mandatory. Yet, in developing countries, SR is still voluntary because there is still no regulation requiring the companies to compile and issue SR. This research aims to find out the development of the mandatory and voluntary instruments related to SR. It is a literature review done using instruments such as a tabulation containing the development of the mandatory and voluntary instruments (government policy). Enthusiasm for the application of SR and commitment, and efforts to achieve transparency and accountability all have increased. Countries with interest in SR have a significant development: 19 countries in 2006, 32 countries in 2010, 45 countries and regions in 2013, and 71 countries and regions in 2016. Indonesia, especially, has its SR regulations that have grown from 180 in 2013 to 400 in 2016, with government regulations dominating 80% of all regulations. Mandatory instruments dominate more than voluntary instruments. The application of SR 30% is for large companies listed on the stock exchange. SR reporting by public companies has covered all sectors on the stock exchange. All were greatly influenced by the role of the government encouraging the companies to disclose information about sustainability in their annual reports. Social reporting instruments show a faster development than environmental reporting instruments.